The politics of international economic law - Broude, Tomer; Busch, Marc L. (Marc Lawrence), 1966-; Porges, Amelia (Cambridge : Cambridge University Press, 2011)
'How do politics and international economic law interact with each other? Financial crises and shifts in global economic patterns have refocused our attention on how the fingerprints of the'visible hand' can be seen all over the institutions that underpin the rules of globalization. From trade and investment to finance, governments are under pressure to enforce, resist, and re-write international economic law. Lawyers have seldom given enough attention to the influence of politics on law, whereas political scientists have had an on-again, off-again fascination with how the law influences relations among states. This book leads the way toward filling this interdisciplinary gap, through a series of important studies written by leaders in the field on specific problems in international economic relations. The book demonstrates a variety of ways in which the international political-economic nexus may be researched and understood'--
Machine generated contents note: 1. Introduction: some observations on the politics of international economic law Tomer Broude, Marc L. Busch and Amelia Porges; Part I. The Politics of Law-Making in International Trade: 2. The politics and indirect effects of asymmetrical bargaining power in free trade agreements Meredith Kolsky Lewis; 3. The politics of linkages in U.S. preferential trade agreements Kimberlee G. Weatherall; 4. The politics of African trade negotiations in the WTO's Doha Round Uche Ewelukwa; 5. The politics of legitimacy in the UNCITRAL working methods Claire R. Kelly; Part II. The Politics of International Investment Treaty-Making: 6. The politics of the European Union's investment treaty-making Marc Bungenberg; 7. The politics of China's investment treaty-making programme Axel Berger; 8. The politics of south-south bilateral investment treaties Lauge Skovgaard Poulsen; Part III. The Politics of Sovereign Wealth and International Financial Law: 9. The politics of sovereign wealth funds: benign investors or smoking guns? Yvonne C. L. Lee; 10. The politics of international financial law Douglas Arner; Part IV. The Politics of Dispute Settlement in International Economic Law: 11. The politics of judicial economy at the WTO Marc L. Busch and Krzysztof Pelc; 12. The politics of competing jurisdictions in WTO and RTA disputes, and the use of private international law analogies Henry Gao and C. L. Lim; Part V. Linkages between International Economic Law and Foreign Policy: 13. The politics of rules of origin Moshe Hirsch; 14. The politics of divestment Perry S. Bechky.
Includes bibliographical references.
Keywords: Foreign trade regulation -- Political aspects; Investments, Foreign -- Law and legislation -- Political aspects